2020
DOI: 10.1111/ane.13285
|View full text |Cite
|
Sign up to set email alerts
|

Subjective postural vertical in Parkinson's disease with lateral trunk flexion

Abstract: Lateral trunk flexion (LTF) is one of the postural abnormalities that can develop in patients with Parkinson's disease (PD). It is an important clinical sign, and it affects activities of daily living and quality of life. 1 Although the pathophysiology of LTF in PD has not been fully clarified, we know that alterations in sensory-motor integration pathways result in abnormal body schema perception and cognition, and this is one of the reasons why patients are unable to appropriately perceive their own physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
(39 reference statements)
2
10
0
Order By: Relevance
“…The SPV ratio is used to evaluate the SPV with reference to the axis of lateral exion, so an SPV ratio of ≥ 1 means that the SPV angle is larger than the LTF angle. In a previously reported longitudinal study, cases in which the SPV angle was larger than the LTF angle were also observed, suggesting use of the SPV ratio as a predictor of the course of LTF (11). Our study, reported herein, veri ed a relation between the SPV ratio and change in the LTF angle at 1 year, con rming potential usefulness of the SPV ratio obtained on initial evaluation as a prognosticator of the course of PD-associated LTF.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The SPV ratio is used to evaluate the SPV with reference to the axis of lateral exion, so an SPV ratio of ≥ 1 means that the SPV angle is larger than the LTF angle. In a previously reported longitudinal study, cases in which the SPV angle was larger than the LTF angle were also observed, suggesting use of the SPV ratio as a predictor of the course of LTF (11). Our study, reported herein, veri ed a relation between the SPV ratio and change in the LTF angle at 1 year, con rming potential usefulness of the SPV ratio obtained on initial evaluation as a prognosticator of the course of PD-associated LTF.…”
Section: Discussionsupporting
confidence: 83%
“…The mean value of these measurements was used as the SPV angle. The SPV ratio was the SPV measured with reference to the axis of lateral exion, and in accordance with preceding studies, was calculated by dividing the SPV angle by the LTF angle (SPV ratio = SPV angle/LTF angle) (11).…”
Section: Informed Consentmentioning
confidence: 80%
See 2 more Smart Citations
“…Thus, to date, sex differences in the effect of posture on gait function in PD patients have yet to be clari ed. Furthermore, it has been hypothesized that subjective vertical position (SPV) [20], which affects forward trunk exion (FTF) and LTF in PD patients, also affects gait [21,22]; however, the in uence of SPV on gait according to sex has not been investigated. This study examined the in uence of posture and vertical perception on gait function in PD patients by sex; to our knowledge, this is the rst such evaluation.…”
Section: Introductionmentioning
confidence: 99%